Daylighting and integrated lighting design - Meek, Christopher (Christopher Martin), 1971-; Van Den Wymelenberg, Kevin G. (Pocket architecture., 2015)
Daylighting and Integrated Lighting Design provides architects, building designers and students clear direction for the successful inclusion of daylight and integrated electric light in buildings. It presents design teams with the performance analysis resources, energy saving estimates and user satisfaction results they need in order to make informed decisions regarding daylighting and lighting design. Written by two well-known experts in the field, the book provides critical geometric and material relationships along with proven design process activities, offered in a quick-reference format, with sufficient context to address the range of associated issues present in any building projectboth the "fundamentals" and "applications" which cover design concepts and practice activities applicable to all integrated lighting projects. Specific directives for how the concepts covered are applied in a range of common design scenarios, including architectural rules-of-thumb, instructions for ensuring visual comfort and preferred approaches for electric lighting control integration. In demonstrating these necessary insights to designers, the authors employ an iterative analysis of common "daylighting patterns" and illustrate and annotate both successful and unsuccessful examples via built form and simulation. Part of the PocketArchitecture Series, this is the ideal pocketbook for any designer serious about reducing the energy impact of their buildings.